Alginate and Chitosan-Based Hydrogel Enhance Antibacterial Agent Activity on Topical Application - Wathoni N; Suhandi C; Ghassani Purnama MF; Mutmainnah A; Nurbaniyah NS; Syafra DW; Elamin KM (Infection and Drug Resistance, 2024)
Nasrul Wathoni,1 Cecep Suhandi,1 Muhammad Fadhil Ghassani Purnama,1 Annisa Mutmainnah,1 Neng Sani Nurbaniyah,1 Desra Widdy Syafra,1 Khaled M Elamin2 1Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, 45363, Indonesia; 2Graduate School of Pharmaceutical Sciences, Kumamoto University, Kumamoto, 862-0973, JapanCorrespondence: Nasrul Wathoni, Department of Pharmaceutics and Pharmaceutical Technology, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, 45363, Indonesia, Tel +62-22-842-888-888, Email nasrul@unpad.ac.idAbstract: Untreated topical infections can become chronic, posing serious health issues. Optimal skin adherence is crucial in addressing such infections. In this context, chitosan and alginate emerge as promising candidates for use as a foundation in the development of topical hydrogels. The aim of this review is to examine the literature on topical hydrogel formulations that use chitosan and alginate as foundations, specifically in the context of topical antibacterial agents. The research methodology involves a literature review by examining articles published in databases such as PubMed, Scopus, ScienceDirect, and Google Scholar. The keywords employed during the research were “Alginate”, “Chitosan”, “Hydrogel”, and “Antibacterial”. Chitosan and alginate serve as bases in topical hydrogels to deliver various active ingredients, particularly antibacterial agents, as indicated by the search results. Both have demonstrated significant antibacterial effectiveness, as evidenced by a reduction in bacterial colony counts and an increase in inhibition zones. This strongly supports the idea that chitosan and alginate could be used together to make topical hydrogels that kill bacteria that work well. In conclusion, chitosan and alginate-based hydrogels show great potential in treating bacterial infections on the skin surface. The incorporation of chitosan and alginate into hydrogel formulations aids in retaining antibacterial agents, allowing for their gradual release over an optimal period. Therefore, hydrogels specifically formulated with chitosan and alginate have the potential to serve as a solution to address challenges in the treatment of topical bacterial infections.Keywords: Alginate, chitosan, hydrogel, topical, antibacterial agent